Contemporary Issues in International Economics - Oplotnik, Zan Jan (2021)
The contemporary economic environment is in most segments quite different than it was even two decades ago. Globalization, development of new technologies, especial in the IT sector, financial innovations, repositioning of economic powers, and new business models are only a few of many new realities. Although all listed brought numerous new possibilities and continuous economic growth, we cannot neglect the increased risks and perils of contemporary economic reality. Uncertainty and adaptation have become a mantra in the life of entrepreneurs, governments, and institutions. Through eight chapters of this monograph, different experts, researchers and scholars try to enlight contemporary economic environment from a different perspective, either from the perspective of entrepreneur, financial industry, governments or average consumer and participant in the modern economy that was very promising only a few decades ago, but more uncertain and dangerous than ever, in the present.